Analisis Kebutuhan Pengembangan Bahan Ajar Mata Kuliah Budaya Lokal Di IAIN Palangka Raya - Jasiah Jasiah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Teaching materials in the learning process plays a very important. If the teacher can utilize the teaching materials as well, then the faculty can share the role with teaching materials. Besides lecturers using appropriate teaching materials can save time in teaching and lecturers can change the role of a teacher becomes a facilitator, and to improve the learning process becomes more effective and interactive. For students, teaching materials can help learners become independent and can be used to measure the competence that has been owned by students. The local culture course is programmed elective courses in the sixth semester of 2017 and listed on the curriculum of Study Program of Madrasah Ibtidaiyah teacher education courses. Teaching materials that have been used in the learning activities is a simple teaching material prepared by the lecturer by using a reference from the internet and books are minimal. The purpose of this study was to determine the needs of students to instructional materials subject to local culture. The research subject was a student from 2017, amounting to 25 data was collected using observation sheets and questionnaires lectures open to students. Observations show that the obstacles encountered in the course of learning the local culture is not teaching materials that can be used as a handle in the learning process. The results of the questionnaire analysis needs of students to instructional materials show that the teaching materials needed by the students is in the form of modules and textbooks.